EVALUATION OF THE PELITA MARKET REVITALIZATION PROGRAM IN IMPROVING THE WELFARE OF TRADERS IN THE CITY OF SUKABUMI - Fadhillah, Agi Rizky; Nur, Tuah; Amirulloh, M. Rijal (DIA: Jurnal Administrasi Publik, 2025)
Study aims to evaluate the Sukabumi City Pelita Market Revitalization Program. The main focus is to understand the revitalization program, its implementation, and its impact on both traders and the local public. Evaluation steps include identifying program successes, challenges faced, and responses to feedback from various stakeholders. Research methods involve descriptive qualitative analysis using techniques such as interviews, observations, and documentation. Informants include the Head of the Sukabumi City Trade Service, PT. Fortunindo Artha Perkasa, and Pelita Market traders. Data is analyzed through reduction, presentation, and drawing conclusions. Research results show the effectiveness of related programs in enhancing the number of traders, sales turnover, and quality of market facilities, although there are diverse views from stakeholders. Efficiency in resource utilization, particularly in technology and optimal budget management, is a primary focus, although challenges in budget management and engagement with third-party parties remain. Adequate support for merchants, including facilities and training, is essential, along with attention to temporary access paths and additional support needs. Economic alignment in the market is crucial, but concerns regarding costs and accessibility persist. Responsibility for addressing trader and public feedback is important for sustainable repair, including market cleanliness and safety. The accuracy of the revitalization program must align with the needs of local traders, society, and aspirational goals, with room for increased responsibility and sustainability in the program, hoping for the involvement of all parties concerned.